Public Disclosure and Dissimulation of Insider Trades - Huddart, Steven; Hughes, John S.; Levine, Carolyn B. (Econometrica, 2001)
Regulation requiring insiders to publicly disclose their stock trades after the fact complicates the trading decisions of informed, rent-seeking insiders. Given this requirement, we present an insider's equilibrium trading strategy in a multiperiod rational expectations framework. Relative to Kyle (1985), price discovery is accelerated and insider profits are lower. The strategy balances immediate profits from informed trades against the reduction in future profits following trade disclosure and, hence, revelation of some of the insider's information. Our results offer a novel rationale for contrarian trading: dissimulation, a phenomenon distinct from manipulation, may underlie insiders' trading decisions.